EPIDEMIC PROCESS IN HOSPITALS HIV INFECTIONS IN THE OF TASHKENT (World Bulletin of Public Health, 2024)
Nosocomial HIV infection refers to infectious diseases that have been transferred or have been arisen in hospital conditions (the sum of infections recorded and those that occurred in the hospital). Nosocomial infection is one of the most severe forms. Therefore, serious attention needs to be paid to nosocomial viral infections. This article provides information on studying the mechanism of development of the epidemic process of nosocomial HIV infection in medical units in the city of Tashkent and improving its prevention.
Keywords: Nosocomial HIV infection; morbidity; infectivity; prevalence